Grain size dependence of twin-dominant deformation in rolled magnesium AZ31 investigated by in situ microscopic image correlation - Uçar, Sevinç. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
In this study, twin-dominant deformation in rolled Magnesium AZ31 is explored with multi-scale in situ digital image correlation (DIC) by parametrizing grain size. Two samples extracted along the rolling direction are used for the grain size comparison: i) fine-grained (FG) sample with ~11 μm, ii) coarse-grained (CG) sample with ~25 μm grain size. The samples are tested under compressive loading that activates the tensile twinning system {101̅ 2}〈1̅ 011〉. Sample surfaces are monitored with macroscopic and microscopic imaging as load is incremented in position control. By area scanning the sample under microscopic optics, macroscopic deformation structures are mapped with microscopic resolution. These ultra-high-resolution maps are used to compare strain distributions of FG and CG samples. In terms of stress response and the distribution of deformation patterns, the effect of grain size is noticeable. The level of stress that FG sample exhibits on the twin plateau (flat section of the stress strain curve) is higher than that of the CG sample (80 and 60 MPa, respectively). Both samples display heterogeneous deformation in the form of ±45° inclined bands. Quantitative analysis of the deformed regions shows that average strains in deformation bands are always higher in FG sample than in CG sample but by a small margin (~10%). The nominal average standalone band strain in the axial direction spans from 1.5 to 2 % to be put in perspective of the 6.5% twin transformation strain. A quantity named sole-twinactivity volume fraction , {u1D449}{u1D446}{u1D447}{u1D434} , is defined over the bands that presumes entire strain accomodation comes from tensile twinning, {u1D449}{u1D446}{u1D447}{u1D434} is slightly higher in FG sample compared to the CG sample by the same ~10% margin. {u1D449}{u1D446}{u1D447}{u1D434} remains constant on a singular band even when it expands, confirming the conjecture that band strain and corresponding {u1D449}{u1D446}{u1D447}{u1D434} are characteristic values. Only when bands intersect and interact, the strain in these localization structures rise noticeably.
Keywords: Magnesium.